Immune correlates of clinical benefit in a phase I study of hyperthermia with adoptive T cell immunotherapy in patients with solid tumors. (29th November 2019) - Qiao, Guoliang; Wang, Xiaoli; Zhou, Xinna; Morse, Michael A.; Wu, Jiangping; Wang, Shuo; Song, Yuguang; Jiang, Ni; Zhao, Yanjie; Zhou, Lei; Zhao, Jing; Di, Yan; et al.
Abstract: Purpose: To characterize the T cell receptor (TCR) repertoire, serum cytokine levels, peripheral blood T lymphocyte populations, safety, and clinical efficacy of hyperthermia (HT) combined with autologous adoptive cell therapy (ACT) and either salvage chemotherapy (CT) or anti-PD-1 antibody in patients with previously treated advanced solid tumors. Materials and methods: Thirty-three (33) patients with ovarian, pancreatic, gastric, colorectal, cervical, or endometrial cancer were recruited into the following therapeutic groups: HT + ACT ( n  = 10), HT + ACT + anti-PD-1 inhibitor (pembrolizumab) ( n  = 11) and HT + ACT + CT ( n  = 12). Peripheral blood was collected to analyze TCR repertoire, measurements of cytokines levels and lymphocyte sub-populations before and after treatment. Results: The objective response rate (ORR) was 30% (10/33), including three complete responses (CR) (9.1%) and seven partial responses (PR) (21.2%) and a disease control rate (DCR = CR + PR + SD) of 66.7% (22 of 33). The most common adverse reactions, blistering, subcutaneous fat induration, local heat-related pain, vomiting and sinus tachycardia, were observed in association with HT. IL-2, IL-4, TNF-α, and IFN-γ levels in peripheral blood were significantly increased among the clinical responders ( p  < 0.05) while IL-6 and IL-10 were elevated among those with progressive disease ( p  < 0.05). Peripheral blood CD8 + /CD28 + T cells increased ( p  = 0.002), while the CD4 + /CD25 + /CD127 + Treg cells decreased after therapy ( p  = 0.012). TCR diversity was substantially increased among the clinical responders. Conclusions: Combining HT with ACT plus either CT or anti-PD-1 antibody was safe, generated clinical responses in previously treated advanced cancers, and promoted TCR repertoire diversity and favorable changes in serum IL-2, IL-4, TNF-α, and IFN-γ levels in clinical responders.